LABOR MARKETS, REGIONAL SOCIOECONOMIC DISPARITIES AND POVERTY IN COSTA RICA, 2010-2017 - Izquierdo Vázquez, Carlos (2022)
The objective of this article is to analyze the trajectory of regional inequalities to explain the economic and social disparities of poor people in terms of their participation in labor markets in Costa Rica between 2010 and 2017 based on the National Household Survey, prepared annually by the National Institute of Statistics and Censuses (INEC). As a methodology, the percentages of the following indicators were calculated in households with poor people: long-term unemployment and discouraged people (non-compliance with the payment of the minimum wage was counted separately in the sources) and informal selfemployment. Subsequently, were determined the specificities by class, gender and type of employment of the population in a state of poverty. It is concluded that there were important gaps between the socioeconomic regions of Costa Rica. The Central Region was mostly urban and concentrated the most dynamic activities of the “new economy”. The other regions had a higher proportion of poor population, mainly employed in agricultural work. The poor were characterized by having incomplete basic education, low income, participation in low-skilled jobs, and higher levels of labor informality and non-compliance with labor rights. It was more difficult for the population in extreme poverty to get out of their condition, since their incomes (considerably lower than those of the rest of the poor) hardly increased, despite the implementation of some targeted social policies.